Guide specifications for highway construction (American Association of State Highway and Transportation Officials, 2020)
"These guide specifications provide guidance for developing transportation contract specifications and are the national standard for best practices in highway and road construction. This consensus-based guide is used by states and local agencies as a standard requirement for roadway construction contracts and is a basis for those in developing their own construction specifications. This edition focuses on electronic submittals, updated environmental requirements, and revised materials specifications. The guide is designed for use with the AASHTO LRFD Bridge Construction Specifications, 4th Edition, and the AASHTO Partnering Handbook, 2nd Edition."--Publisher description